Improving the Students’ Ability in Speaking by Using Debate Technique at the Tenth Grade of SMK Negeri 1 Aramo - bestari laia (Scope : Journal of English Language Teaching, 2020)
This research is done at SMK Negeri 1 Aramo. The subject of this research is the tenth grade which consists of 16 students, 8 girls and 8 boys. While the objects of this research are the implementation of Debate Technique, and the students’ ability in speaking. It is conducted by using Classroom Action Research (CAR) that consists of four stages in each cycle. They are planning, action, observation, and reflection. The data will be analyzed in qualitative data and quantitative data.The result of the data analysis in the first cycle is not satisfied. That’s why, the researcher continues to the second cycle. In the second cycle, the students get improvement in speaking. One student (6%) in the less level, 4 students (25%) in adequate level, 11 students (69%) in good level. The average of the students’ score is 65. Then, the result of field notes in the first meeting, the percentage of the students who are active is 75%, creative is 69%, and cooperative is 63%. While, in the second meeting, the percentage of the students who are active is 94%, creative is 94%, and cooperative is 100%. The average of the students’ score in the second cycle gets improvement and reaches the Minimum Competence Criterion (MCC) target fixed at the tenth grade of SMK Negeri 1 Aramo. Then, the researcher does not continue the research to the next cycle.From the result of this research, the researcher concludes that Debate Technique is an active and creative learning process in teaching speaking, working in a group and also sharing knowledge and ideas to others.